The impact of banking digital transformation on financial inclusion in Vietnam: Empirical evidence from the digital ERA - Nga, Nguyen Thi Viet; Hang, Pham Thi Thuy; Tuan, To Van; Tuan, Tran Viet (Edelweiss Applied Science and Technology, 2026)
In the context of digital transformation reshaping financial systems worldwide, this study examines the impact of banking digital transformation on financial inclusion in Vietnam during the period 2016-2025, with particular attention to the transmission mechanisms through eKYC adoption and SMEs’ access to credit. A multi-method empirical framework is employed, combining Data Envelopment Analysis (DEA) to construct the Digital Banking Efficiency Index (DBEI), System Generalized Method of Moments (System-GMM) to estimate the dynamic effects of digital transformation on financial inclusion, and Partial Least Squares Structural Equation Modeling (PLS-SEM) to test mediating relationships. The findings show that banking digital transformation has a positive and statistically significant effect on financial inclusion. Banks with higher digital transformation efficiency tend to expand financial service accessibility, improve SMEs’ credit access, and enhance digital customer onboarding. The results further confirm that eKYC serves as a partial mediator in the relationship between digital transformation and financial inclusion. This study concludes that banking digital transformation is not merely a process of technological modernization but a key driver of inclusive financial development in Vietnam. The findings offer practical implications for strengthening digital infrastructure, promoting eKYC, improving data governance, and developing digital credit solutions for SMEs.